ADMINISTRASI SEKOLAH (ADMINISTRASI KEUANGAN SEKOLAH DAN SARANA PRASARANA) - Sity Fatimah; Al-Hidayah; Tiangat Siregar; Sumiati; Nurhayati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Financial administration and equipment are carried out as an effort to improve the quality of education in schools. The method used in writing this journal is qualitative by using literature studies, namely by searching for and analyzing journals or reading sources related to the jornal being discussed. In carrying out educational supervision, financial administration, equipment must be considered. Apart from that, improving the relationship between the school sphere and relations with the community also needs to be improved in order to establish supervision in the world of education that is based on improving the quality of education in schools. In educational supervision, there needs to be a model or strategy to expand the scope of research. In this case, financial administration and equipment are implemented in an effort to improve the quality of education in schools